Tuning donor level of nitrogen-doped diamond by deep strain engineering—An ab initio study - Yang, Limin; Fan, Rong; Hu, Alice; Ma, Junzhang; Liu, Yingxia; Lu, Yang (Applied physics letters, 2023)
The development of diamond semiconductor devices has been hindered by the challenge of preparing n-type diamond with a shallow donor state. Recently, elastic strain engineering has emerged as a promising strategy for modulating the electrical properties of diamond. In this study, we used first-principles calculations to investigate the influence of large, uniaxial elastic strain on the electrical properties of nitrogen (N)-doped diamond, particularly the donor level. We found that both tensile and compressive strains can shift the donor level of N to a shallower state, but compressive strains of more than 9% along [100] appear more effective in making N a shallower donor in strained diamond. This study offers insights for future experimental design to combine strain engineering and doping toward practical diamond semiconductor devices.